Peran Pameran IFEX 2024 dalam Pengembangan Kompetensi dan Inovasi Mahasiswa Desain Interior di Universitas Pradita - Harlis Setiyowati; Widasapta Sutapa; Rizki Kurniawan (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
The IFEX 2024 exhibition marks an important milestone in advancing competence and innovation in the field of interior design in Indonesia. With a focus on student participation, the exhibition not only showcases their creative works but also serves as a platform to enhance their understanding of the dynamic interior design industry. This article explores the role of the IFEX 2024 exhibition in facilitating education, innovation, and partnerships for sustainable development. Through meetings between students, industry practitioners, and other stakeholders, the exhibition encourages cross-sector collaboration to create sustainable and competitive design solutions. With a focus on related SDGs, such as quality education, inclusive economic growth, and sustainable city development, this article underlines the importance of the IFEX 2024 exhibition in building a better future for the Indonesian interior design industry, especially Pradita University students.